Basic Concepts Of Education Policy And Innovation In Mtsn-2 Tapanuli Tengah - Putra Mahendra Gunawan Nasution; Wandana Simatupang; Syafaruddin; Makmur Syukri (Institute of Computer Science (IOCS), 2022)
The government has regulated the quality assurance of education in Law Number 19 of 2005 concerning National Education Standards as an educational policy and innovation that must be applied to all levels of education. This research applies qualitative descriptive methods and approaches to examine social conditions, and phenomena by means of description. The data analysis used by researchers is the analysis of initial data in the field, data analysis while in the field, and data analysis after in the field. The data collection procedure in this study went through 3 stages, namely observation, interviews, and documentation. The source of the data was obtained by researchers directly from the madrasah leaders, both madrasah heads and deputy heads of madrasahs and administrative departments which can be categorized as primary data and secondary data. The results of the study revealed that MTsN-2 Tapanuli Tengah has implemented national education standards properly, optimally, and optimally. The curriculum innovation used is also in accordance with government policy, namely the 2013 curriculum which focuses on students interests, talents, and abilities, this aims to improve self-development in students and prepare high-quality students.